Analysis of sustainability aspects of sanitation planning approaches in urban peri-urban area of Nepal - Sherpa, Mingma Gyalzen; Thammarat Koottatep; Chongrak Polprasert; Soparth Pongquan; Luethi, Christoph; Shrestha, Roshan Raj; Swiss National Center for Competence in Research, Global (NCCR) North South; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
This research study analyzed the different community based sanitation planning approaches in Nepal. As part of the research the HCES planning approach was validated through an action research toidentify challenges, constrains, strengths and weaknesses. The study also analyzed the sanitation planning processes of two selected agencies working in the urban sanitation sector i.e. the Small Towns Water Supply and Sanitation Sector Project funded by ADB/Government of Nepal and the Siddhipur Integrated Water andSanitation Programme in Siddhipur, a project of UN-HABITAT. Multiple case study analysis approach using both primary and secondary data collection method was adopted to conduct the study. The three sanitation planning approaches were compared to analyze the processes involved, to measure the performance of sanitation service outcomes and sustainability provisions. The results from the analysis were used to determine the similarities and differences of the planning approaches and factors governing success and shortcomings to attain effective sanitation services. Some of the key challenges based on the validation of the HCES planning were the time requirement to facilitate a participatory planting process, the limitation to determine an optimum ideal levelof stakeholder participation, the requirement address cross-sectoral development needs beyond the scope of sanitation and the need to balance between rational criteria based decision and consensus decision making process. Likewise, the strengths of the approach were the flexibility to facilitate stakeholder participation to build a democratic process, the ability to integrate different waste streams into the planning framework, and its ability to develop a realistic sanitation plan to pool in local and external funds for implementation. Absence of a secured financing mechanism to operationalize HCES plan, weak local institutional capacity and limited possibilities to institutionalize the approach were some of the critical factors for scaling up the approach. The well-structured planning approaches like HCES showed better performance over other planning processes. Comparison of the sanitation process and outcomes in the three cases showed that stakeholder participation was better in the HCES case as compared to others, planning duration in the three case studies ranges from 1-2 years. While the average per capita investments were between USD 74-76 per capita in all the three cases, the resulting outcomes of the investments were significantly different. Faecal sludge management provisions were found to be poor Khairenitar and Siddhipur. Organic waste management was so far not a grave problem. Similarly, grey water was mostly managed by households by discharging in the backyard, common in all the three cases. Storm water drainage provisions were fund inadequate in all cases. These conditions show that the government{u2019}s and donor{u2019}s focus on urban sanitation in small towns and peri-urban areas still had a limited impact on sanitation. Theentire sanitation value chain components were not addressed. There is an urgent need for institutionalized support from the government to address the sanitation situation especially with reference to sanitation system components. These aspects need to be institutionalized within decentralized service delivery mechanisms. To uplift the status of sanitation there is a high need to prioritize sanitation and increase investments. Towns and settlements need to develop citywide sanitation plans as a first step to systematically address urban sanitation issues.
A dissertation submitted in partial fulfillment of the requirements for the degreeof Doctor of Technical Sciencein Environmental Engineering and Management
Thesis (Ph.D.) - Asian Institute of Technology, 2016
Keywords: Sustainability; Sanitation -- Nepal; Nepal -- Environmental aspects; Sanitation -- Environmental aspects; Water-supply -- Sanitation -- Nepal